Systemic analysis and theoretical-game tools of interaction between economic, legal and social national macrosystems - L. V. Zhukovskaya (Russian Journal of Economics and Law, 2019)
Objective: economic and legal description, formal justification and construction of models of the balanced economic, legal and social macrosystems in order to determine effective strategic decisions under uncertainty.Methods: the theoretical and methodological basis of the study is the synthesis of the provisions and principles of game and management theories, economic and mathematical modeling and the game-theoretical models of decision-making in complex systems developed on their basis, as well as theoretical and methodological approaches of system analysis, economics, sociology, and law.Results: the balance of economic, legal and social systems is determined by the target orientation to the growth of the population’s well-being. The existing mechanisms for achieving this balance do not take into account the interests of all participants of the systems. The paper presents a structural analysis of the interaction and mutual influence of economic, legal and social macrosystems (a complex metasystem); the necessity of transforming the existing approaches to their regulation is shown. The problem of ensuring the systems’ balancing is largely related to the conflict of interests of the parties. Therefore, traditional methods of modeling decision-making processes do not reflect the real socio-economic processes. This problem was solved through game-theory models that contribute to the implementation of the constitutionally established norms which define Russia as a social state. When making strategic decisions in the social sphere, it is proposed to use the concept of the Golden rule of morality as the main economic doctrine, instead of the currently used neoliberal approach, based, among other things, on the concept of Nash equilibrium. The equilibrium models of the complex metasystem by Nash and Berge were formalized, constructed and compared.Scientific novelty: in contrast to the Nash equilibrium (principles of rationality) - the traditional approach used in the construction of equilibrium models, - the paper offers a theoretical justification of the development and construction of equilibrium models and balance sheet equilibrium of economic, legal and social macrosystems by Berge, as well as a formalization of effective strategic decisions and their respective risks.A distinctive feature of the constructed macromodels is the use of the philosophical and moral concept of the Golden rule (the mathematical basis is the balance by Berge) as an economic doctrine for strategic decision-making under uncertainty, and the construction of the so-called guaranteed optimal solutions by Pareto (effective), based, among other things, on the concept of the pair “social guarantee - life risk”. If, in real conditions, one of the macrosystems is economic and is a “generator” of uncertainties, a guaranteed solution is formalized, optimal by Slater (weakly effective).Practical significance: the developed methodology for building the system equilibrium of economic, legal and social macro-systems enables to make decisions socially significant for the population that adequately take into account the peculiarities of the modern socio-economic macro-systems, such as nonstationarity, dysfunctionality, incomplete information, inconsistency, conflict, alternatives, multicriterial character, and risk; and to develop assisting intellectual systems of supporting decision-making based on mathematical models built using the game-theory approach.